FAMÍLIA ESCRAVA NUMA BOCA DO SERTÃO.LENÇÓES, 1860-1888 (Revista de História Regional, 2007)
By using information taken from inventories (registers) and wedding certificates of free and slave people, this abstract talks about the existence of slave families in Lençóes by the time this village was a boca do sertão (hinterland access), a conflicting area between the white settlers and the remaining indians who inhabited western São Paulo Province in the middle of the nineteenth century. Differently from what traditional history has emphasized, the slaves formed their families even under difficult conditions in which they lived. In Lençóes, about one third of the adult, slave population over 15 listed on the inventories was or had been married before. Some groups of this village were formed exclusively by families. The wedding certificates also carried the familys mark: more than half of the slave population had, at least, their ancestors name, which was the official recognition of kinship among them.